"المساهمة في تحسين خصائص خرسانة رمل الآبار البترولية " - محمــد, شايبــي; محمد الأميــن, زايـــد; جعفــــر, سالمــي (University of El-Oued, 2021)
"The oil fields in southern Algeria, especially in the Hassi Messaoud region, suffer from the problem of sand accumulation resulting from the process of drilling and prospecting for oil, and the environmental pollution that is dangerous to humans and nature. Also, the oil companies located in these areas suffer from the problem of scarcity and the distance of suitable sand for construction from where they are located, for use in some constructions related to the nature of their work. Several international studies have been conducted, most of which state the danger of leaving the drilling material and sand mixed with it so important in the exploration areas In this regard and in the context of this idea, we decided during this study to try to answer the possibility of using oil well sand as an alternative, even partially, in construction to reduce these phenomena and the problems arising from them in the fields of Hassi Messaoud region. As well as contributing to improving the mechanical and physical properties (pressure resistance, bending resistance, shrinkage phenomenon) of petroleum well sand concrete. Through the most important results obtained, represented in a significant improvement in pressure resistance and in the event of shrinkage, we open the development and improvement of oil well sand concrete, with the aim of reaching the generalization of the use of these huge quantities of this sand located in the Hassi Messaoud region in the field of construction, as well as the elimination of environmental pollution, and that In the medium and long term. " "تعاني حقول النفط بالجنوب الجزائري وخاصة بمنطقة حاسي مسعود من مشكل تكدس الرمال الناتجة عن عملية الحفر والتنقيب عن البترول وما تشكله من تلوث بيئي خطير على الإنسان والطبيعة. وكذلك تعاني الشركات النفطية الموجودة في هذه المناطق من مشكل قلة وبعد الرمال الصالحة للبناء عن مكان تواجدها وذلك لاستعمالها في بعض الإنشاءات المتعلقة بطبيعة عملها. أجريت عدة أبحاث عالمية تنص في معظمها على خطورة ترك مادة سائل الحفر والرمال المختلطة بها هكذا مهملة في مناطق التنقيب. في هذا الصدد وفي سياق هذه الفكرة ارتأينا خلال هذه الدراسة محاولة الإجابة عن إمكانية استعمال رمل آبار البترول كبديل ولو جزئيا في البناء للتقليل من هذه الظواهر والمشاكل المترتبة عليها في حقول منطقة حاسي مسعود. وكذلك المساهمة في تحسين الخصائص الميكانيكية والفيزيائية (مقاومة الضغط مقاومة الانحناء ظاهرة الانكماش) لخرسانة رمل آبار البترول. ومن خلال أهم النتائج المتحصل عليها والمتمثلة في تحسن معتبر في مقاومة الضغط وفي حالة الانكماش فإننا نقترح تطوير وتحسين خرسانة رمل آبار البترول وهذا بهدف الوصول إلى تعميم استعمال هذه الكميات الهائلة من هذه الرمال المتواجدة في منطقة حاسي مسعود في مجال الإنشاءات وكذلك القضاء على التلوث البيئي وذلك على المدى المتوسط والبعيد. "
Matéreaux en génie civil مذكرة ماستر تخصص
Keywords: Drilling fluid, petroleum well sand, sand concrete, bending resistance, pressure resistance, shrinkage.; سائل الحفر، رمل الآبار البترولية، خرسانة الرمل، مقاومة الانحناء، مقاومة الضغط، الانكماش.